Bronchial disease in ulcerative colitis. Issue 8 (August 1980) - Higenbottam, T; Cochrane, G M; Clark, T J; Turner, D; Millis, R; Seymour, W
Abstract : Ten patients with ulcerative colitis, all of whom were non-smokers, presented with a productive cough. In six, the chest radiography was normal and cough was the only symptom; three of these patients had a minor obstructive ventilatory defect on testing. Four patients complained of exertional dyspnoea and had both an abnormal chest radiograph with bilateral pulmonary shadows and a mixed obstructive and restrictive ventilatory defect. Bronchial epithelial biopsies from four patients (two with and two without pulmonary shadows) revealed basal reserve cell hyperplasia, basement membrane thickening, and submucosal inflammation, changes more usually associated with cigarette smoking. Inhaled beclomethasone diproprionate relieved cough in seven patients. The occurrence of airway epithelial disease in association with ulcerative colitis raises the possibility of a systemic mechanism affecting both bronchial and colonic epithelium. It does not seem likely that sulphasalazine was the cause of the pulmonary syndrome in these subjects.